Admirator „rodowitego języka”, zatroskany purysta językowy, baczny obserwator „Polaków amerykańskich”… Wokół refleksji językowych utrwalonych w Listach z podróży do Ameryki Henryka Sienkiewicza - Węgorowska, Katarzyna (Acta Universitatis Lodziensis. Folia Linguistica, 2016)
The text is devoted to those Sienkiewicz’s letters-features, letters-reports, letterscommentaries, letters-articles, letters-reviews in which the author of Quo vadis: 1) verbalizes the situations of the „American Polish people” in the contemporary United States of America, 2) describes the Polish language they used, 3) expresses anxiety about its state, 4) analyzes the phenomenon of denationalization of the compatriots living abroad, 5) pays attention to the progressive Germanization and the linguistic-cultural Anglicization, 6) shows conflicts in the Polish organizations and institutions in America, 7) displays attachment to the Polish language of Helena Modrzejweska – distinguished theatrical personality. Letters from a journey to America (Listy z podróży do Ameryki) is a source of very valuable and diverse (also linguistic) information about the life of the 19th century Polish diaspora in America struggling not only with the material, but also spiritual, including linguistic, problems.